2012
DOI: 10.1080/17470218.2011.634915
|View full text |Cite
|
Sign up to set email alerts
|

Producing and recognizing words with two pronunciation variants: Evidence from novel schwa words

Abstract: This study examined the lexical representations and psycholinguistic mechanisms underlying the production and recognition of novel words with two pronunciation variants in French. Participants first learned novel schwa words (e.g., /ʃənyk/), which varied in their alternating status (i.e., whether these words were learned with one or two variants) and, for alternating words, in the frequency of their variants. They were then tested in picture-naming (free or induced) and recognition memory tasks (i.e., deciding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…For Sóller listeners, the representation of these same words includes [u], their own dialectal form, and [o], the form characteristic of the dialects that surround their own. The multiplicity of phonetic forms linked to a single lexical representation displayed by the Sóller listeners in our study does not need to be different in nature from that which has been revealed by prior studies on the processing of reduced or lenited speech (Bürki et al, 2011(Bürki et al, , 2010Bürki & Frauenfelder, 2012;Connine et al, 2008;Deelman & Connine, 2001;LoCasto & Connine, 2002;McLennan et al, 2003;Pitt, 2009;Ranbom & Connine, 2007;Sumner & Samuel, 2005) .…”
Section: Interpretation and Implicationsmentioning
confidence: 43%
See 1 more Smart Citation
“…For Sóller listeners, the representation of these same words includes [u], their own dialectal form, and [o], the form characteristic of the dialects that surround their own. The multiplicity of phonetic forms linked to a single lexical representation displayed by the Sóller listeners in our study does not need to be different in nature from that which has been revealed by prior studies on the processing of reduced or lenited speech (Bürki et al, 2011(Bürki et al, , 2010Bürki & Frauenfelder, 2012;Connine et al, 2008;Deelman & Connine, 2001;LoCasto & Connine, 2002;McLennan et al, 2003;Pitt, 2009;Ranbom & Connine, 2007;Sumner & Samuel, 2005) .…”
Section: Interpretation and Implicationsmentioning
confidence: 43%
“…Several studies have tried to assess the impact of this type of variation on lexical processing. The focus so far has been on a small set of processes including word-final /t/ and /d/ glottalization (Deelman & Connine, 2001; Sumner & Samuel, 2005), /t/ and /d/ tapping (McLennan, Luce, & Charles-Luce, 2003), nasal flapping (Pitt, 2009; Ranbom & Connine, 2007) and schwa elision in American English (Connine, Ranbom, & Patterson, 2008; LoCasto & Connine, 2002) and French (Bürki, Alario, & Frauenfelder, 2011; Bürki, Ernestus, & Frauenfelder, 2010; Bürki & Frauenfelder, 2012). One of the main questions touched upon by this body of literature is whether all word variants, including the reduced or lenited forms, are equally effective at tapping into lexical representations in on-line spoken-word recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Participants gave more looks to the picture of a pear as the VOT of the initial consonant approached the categorical boundary, which was taken as evidence that fine-grained phonetic differences within a phonemic category impact on word identification. (For similar conclusions based on other typicality effects, including vowel typicality, see Bürki & Frauenfelder, 2012 ; McMurray, Aslin, Tanenhaus, Spivey, & Subik, 2008 ; Trude & Brown-Schmidt, 2012 . See also Andruski, Blumstein, & Burton, 1994, for prototypicality effects in semantic priming).…”
Section: Part 2: Reconsideration Of Psycholinguistic Challenges To Phmentioning
confidence: 52%
“…In these experiments, we combined three experimental methodologies: a novel-word learning paradigm, a picture-naming task, and visual-world eye-tracking. As discussed above, the novel-word learning paradigm has previously been employed in combination with a picture naming task in order to study the production of reduced pronunciation variants (e.g., Bürki & Frauenfelder, 2012; Bürki et al, 2012). Other studies (e.g., Magnuson, Tanenhaus, Aslin, & Dahan, 2003; Sulpizio & McQueen, 2012) have combined novel-word learning with the visual-world paradigm in order to investigate the time course of the recognition of spoken words that have just been learnt.…”
Section: Introductionmentioning
confidence: 99%